Influence of out-side class english activities towards the students’ achievement in learning english for the eleventh year of SMA NW Mataram, academic year 2021/2022 - M. Afan Afan (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
This study aimed at finding out The Influence of Out-Side Class English Activities Towards The Students’ Achievement In Learning English for the Eleventh Year of SMA NW Mataram, Academic Year 2021/2022. The writer took one class of the population (class XI A with 40 students) as the sample of this study. The data of the study were obtained from the observation, questionnaire, English test and interview. Data were analyzed using descriptive qualitative and quantitative method. The t-test used to test the average of the two groups of paired-sample. From the research result it found out that (1) from the data analysis, it was found that the out-side class English activities increase the student’s motivation, interest and attitude in learning English with 84,2% (34 students) prefer joining thse out-side English activities that increase their motivation, attitude and interest. Event only 15,8% (6 students) dislike joining its. (2) From the students’ statements, they (75,8% / 30 students) are prefer joining the out-side class activities since they had more chances to develop their English proficiency. It also given them to use its facility freely. Furthermore, they had so many friends to communicate in kinds of out-side class English activities like in the English speaking zone.(3) The research data proved that out-side class English activities influenced the students’ achievement in learning English. This was caused by the fact that calculated t-value (5,92) was higher than table t value (1,960). Furthermore, it was shown that the students’ average before joining out-side class English activities was higher than average after joining its activities towards the students achievement in learning English.